Protective Effect of Schisandrin on CORT-Induced PC12 Depression Cell Model by Inhibiting Cell Apoptosis In Vitro. (11th May 2022) - Yang, Liu; Wang, Yeqiu; An, Lifeng; Zhang, Xinya; Wang, Jing; Wang, Yi; Cheng, Ruyang; Li, Chenxiang; Ma, Wei
Abstract : Background . In recent years, the incidence of depression is on the rise. Our paper proposed to study the protective effects of Schisandrin on CORT-induced PC12 depressive cell model and the underlying mechanisms. Methods . The in vitro models of PC12 were established using corticosterone (CORT). 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) method was used to screen the effective concentration of Schisandrin, and the models of PC12 were treated with low, medium, and high concentrations of Schisandrin. The cell activity of each group was detected by MTT assay. The LDH activity in each group of cells was detected by lactate dehydrogenase (LDH) kit. Apoptosis rate of each group was detected by Annexin V-FITC apoptosis assay kit. Mitochondrial membrane potential of each group of cells was detected by mitochondrial membrane potential kit. The protein expression levels of Caspase-3, Bax, and Bcl-2 in each group of cells were detected by western blot. Results . The treatment of Schisandrin significantly increased the cell viability in models of PC12. In addition, the results of LDH activity suggested that Schisandrin significantly reduced LDH content in models of PC12. Consistently, Schisandrin reduced the mitochondrial membrane potential of CORT-induced PC12 depressive cell model. Furthermore, Schisandrin effectively reduced the number of apoptotic cells and inhibited the expression of proapoptotic-related proteins (cleaved Caspase-3 and Bax) but increased the antiapoptotic-related protein (Bcl-2) in the models of PC12. Conclusions . Protective effects of Schisandrin on CORT-induced PC12 depressive cell model by inhibiting cells apoptosis in vitro.